Imaginaries of the Brazilian DiplomaticDiscourse: the Celso Amorim’s Official Utterances (Revista de Estudos da Linguagem, 2025)
This study examines the frequency and manner in which Celso Amorim mobilizes left-wing sociocultural imaginaries in his official discourses, considering Charaudeau’s (2016) semiolinguistic perspective. As part of a broader research project analyzing 20 years of official discourses by Brazilian chancellors – from the first Lula government to the Bolsonaro administration – this article specifically focuses on Celso Amorim and on the theme of political ideology. The research is based on theoretical categories of discourse analysis, particularly Charaudeau’s (2016) model, and incorporates the notion of Culture Wars, as conceived by Hunter (1991), to explore ideological tensions in diplomatic discourse. Initially, the study sought to catalog the constants of the so-called “Rhetoric of Cultural War,” a category of analysis we developed for examining discursive clashes in polarized contexts such as culture wars. Subsequently, after describing the quantitative findings, representative excerpts of the results were qualitatively analyzed through the lens of the aforementioned theoretical frameworks. The conclusions indicate that Amorim consistently employed a left-wing political discourse, albeit without adopting a confrontational approach, aligning with the traditional pragmatism and universalism of Brazilian diplomacy. This study thus aims to contribute to the understanding of Brazilian diplomatic discourse – a field still little explored in linguistic studies – while also offering reflections on the ideological dimensions of foreign policy rhetoric conveyed in these discourses.